Determinant of Covid-19 Prevention Behavior in The Community in Pamulang, South Tangerang in 2021 - Munaya Fauziah Fauziah; Oswin Yohsa Ibrahim; Nur Romdhona; Ernyasih Ernyasih (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by SARS-CoV-2. Preventive behavior in the community is important to maintain health during a pandemic. This study aims to determine the determinants of COVID-19 prevention behavior in the community in Bambu Apus, Pamulang in 2021. The approach was conducted in RW. 001 Bambu Apus in June-July 2021 with 180 respondents and using the Probability Proportional to Size Sampling (PPS) sample method. Characteristics of respondents found that the majority of respondents were 36-45 years old (33.3%), with female gender (59.4%), high school education (51.1%), work as private employees (40.6%). Based on the results of univariate analysis, it was found that respondents aged 40 years (55.6%), female (59.4%), had higher education (92.8%), worked (62.2%), good knowledge ( 80%), positive attitude (78.3%), sources of information sourced from social networks (60%), good family support (55%), good health worker support (61.1%) and COVID-19 prevention behavior good (85%). Based on the results of the bivariate analysis, it was found that there was a significant relationship between knowledge (p-value = 0.000), attitudes (p-value = 0.000), family support (p-value = 0.000), health worker support (p-value = 0.000) and behavior. prevention of COVID-19. However, there was no relationship between age (p-value = 0.529), gender (p-value = 0.848), education (p-value = 0.417), occupation (p-value = 0.155), source of information (p-value = 1,000 ), with COVID-19 preventive behavior. Suggestions related to the results of the research are expected that RW administrators can work together with health workers to increase knowledge, attitudes, and family support related to COVID-19 prevention behavior by encouraging, reminding, and educating the public regarding COVID-19.